Unified Social Assistance System - SUAS:: implementation challenges of CRAS in the municipality of Groaíras / Ceará - Ximenes, Maria Elianice Viana (2014)
This article deals with politics of social assistance, considering as reference of analysis the process of consolidation of Single System of Social Assistance (SUAS), from investigation of challenges to execute and implement the system through municipal administration, and more specifically, through Reference Center of Social Assistance (CRAS), in Groaíras/Ceará/Brasil. The relevance of this study for 2 Academy consists in expanding debate whose productions stimulate the spread of innovative ideas and postulates that may contribute with significant advances in view of the importance of understanding the social assistance policy is acquiring in Brasil, through cash transfer programmes with emphasis in consolidation of SUAS and still to contribute to dissemination of knowledge among professionals that study or help in implementation of social policy, making possible a better comprehension about the full achievement of SUAS. Methodologically this work appears as article content review of master´s degree dissertation of the same author, submitted to Universidade Estadual do Ceará (UECE), in the Master Course in Planning and Public Policies, whose limits and possibilities are considered in theoretical validity for the purpose of this article.